2017
DOI: 10.1503/cmaj.170088
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal suicide in Ontario, Canada: a 15-year population-based study

Abstract: BACKGROUND:Death by suicide during the perinatal period has been understudied in Canada. We examined the epidemiology of and health service use related to suicides during pregnancy and the first postpartum year. METHODS:In this retrospective, population-based cohort study, we linked health administrative databases with coroner death records (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) for Ontario, Canada. We compared sociodemographic characteristics, clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 24 publications
(22 reference statements)
4
90
0
8
Order By: Relevance
“…The overall rate of self-inflicted injury in this study was similar to rates reported previously in high-income countries such as the United States and the United Kingdom but no previous studies on self-inflicted injury in immigrant women were identified for comparison. 4,30,31 Since immigrant women have high rates of postpartum depression, a major risk factor for suicidality, the reason why the risk for this outcome was not elevated in immigrant women is unclear. 15,32,33 The causes of severe postpartum mental illness (i.e., illness that might result in suicidality) may be mediated more by biological (i.e., genetic sensitivity to rapid hormonal shifts) than socioenvironmental stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of self-inflicted injury in this study was similar to rates reported previously in high-income countries such as the United States and the United Kingdom but no previous studies on self-inflicted injury in immigrant women were identified for comparison. 4,30,31 Since immigrant women have high rates of postpartum depression, a major risk factor for suicidality, the reason why the risk for this outcome was not elevated in immigrant women is unclear. 15,32,33 The causes of severe postpartum mental illness (i.e., illness that might result in suicidality) may be mediated more by biological (i.e., genetic sensitivity to rapid hormonal shifts) than socioenvironmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…1 Suicidal thoughts are common among women after they give birth, affecting as many as 9% of women, 2 and suicide accounts for a high proportion of maternal deaths globally. 1,3,4 Assault, mainly by intimate partners, affects up to about 13% of women perinatally 5 and is also responsible for some maternal mortality. [6][7][8][9] Immigrant women contribute one-quarter to one-third of births in high-income countries, 10 but their risk for intentional injury in the postnatal period is unknown.…”
mentioning
confidence: 99%
“…3,4 Knowledge about the epidemiology of suicidal behaviour during pregnancy, including the causes and consequences of suicidal behaviour, is critical to inform suicide prevention strategies for pregnant women, and ultimately to reduce maternal mortality. 5 Although suicidal behaviour in pregnancy has been studied for decades, very few studies [6][7][8][9][10][11][12][13] have provided information on the associations of antepartum suicidal behaviour with infant and obstetric outcomes. 10,12 The majority of past studies have focused on suicide attempt by drug overdose.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Nonfatal suicidal thoughts and behaviours (hereafter referred to as “suicidal behaviour”), including suicidal ideation, plan, and attempt, are the strongest predictor of suicide . Knowledge about the epidemiology of suicidal behaviour during pregnancy, including the causes and consequences of suicidal behaviour, is critical to inform suicide prevention strategies for pregnant women, and ultimately to reduce maternal mortality …”
Section: Introductionmentioning
confidence: 99%
“…Suizid ist die häufigste Todesursache unter Müttern innerhalb eines Jahres nach der Geburt [35]. Nur wenige Studien haben sich bisher mit dem Suizid von Müttern nach der Geburt beschäftigt.…”
Section: Suizid Und Gefährdung Des Kindesunclassified